2016
DOI: 10.2807/1560-7917.es.2016.21.5.30124
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of influenza A(H1N1)pdm09 genogroup 6B and drug resistant virus, India, January to May 2015

Abstract: To investigate the aetiology of the 2015 A(H1N1)pdm09 influenza outbreak in India, 1,083 nasopharyngeal swabs from suspect patients were screened for influenza A(H1N1)pdm09 in the state of Madhya Pradesh. Of 412 positive specimens, six were further characterised by phylogenetic analysis of haemagglutinin (HA) sequences revealing that they belonged to genogroup 6B. A new mutation (E164G) was observed in HA2 of two sequences. Neuraminidase genes in two of 12 isolates from fatal cases on prior oseltamivir treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 10 publications
5
52
2
Order By: Relevance
“…For 150 viruses, reported in strain-based manner, both genetic and antigenic data were available. Analysis of A(H1N1)pdm09 HA gene sequences from 12 countries (Czech Republic, Finland, Greece, Ireland, Netherlands, Norway, Portugal, Romania, Russia, Slovenia, Spain and Sweden) reported to TESSy, with provision of accession numbers in publicly accessible databases, confirmed that all these analysed viruses possessed the signature amino acid variations that define subgroup 6B viruses: D97N, K163Q, S185T, K283E and A256T [7][8][9]. All 215 analysed sequences, apart from two viruses isolated in Russia, also carried P83S and I321V substitutions in HA1.…”
Section: Virus Characterisationmentioning
confidence: 95%
See 2 more Smart Citations
“…For 150 viruses, reported in strain-based manner, both genetic and antigenic data were available. Analysis of A(H1N1)pdm09 HA gene sequences from 12 countries (Czech Republic, Finland, Greece, Ireland, Netherlands, Norway, Portugal, Romania, Russia, Slovenia, Spain and Sweden) reported to TESSy, with provision of accession numbers in publicly accessible databases, confirmed that all these analysed viruses possessed the signature amino acid variations that define subgroup 6B viruses: D97N, K163Q, S185T, K283E and A256T [7][8][9]. All 215 analysed sequences, apart from two viruses isolated in Russia, also carried P83S and I321V substitutions in HA1.…”
Section: Virus Characterisationmentioning
confidence: 95%
“…Noteworthy, 80% of the analysed HA sequences have gained a potential glycosylation site S162N. No D222G/E/N substitutions were detected, nor N129D which was recently identified in India in two severe or fatal cases [9]. If the emerging groups continue to diversify from the vaccine component, their antigenic properties may change and the vaccine effectiveness might be reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that these mutations may have caused the disease severity of 2015 outbreak [11]. Recently, another study from central India reported a new mutation E164G in HA2 sequences [12]. …”
Section: Introductionmentioning
confidence: 99%
“…In 2014-2015, A(H1N1pdm09) activity was variable with notable widespread outbreaks in the Indian subcontinent and in parts of Africa (Parida et al, 2016;Takashita et al, 2016). The phylogenetic tree for the HA gene of H1N1pdm09 viruses can be divided into nine major genetic groups, although recently isolated viruses belong to group 6.…”
Section: Discussionmentioning
confidence: 99%